Climate Neutral and Resilient Farming Systems Practical Solutions for Climate Mitigation and Adaptation - Nagothu, Udaya Sekhar (Earthscan Food and Agriculture, 2023)
This book presents evidence-based research on climate-neutral and resilient farming systems and further to provide innovative and practical solutions for reducing greenhouse gas emissions and mitigating the impact of climate change. Intensive farming systems are a significant source of greenhouse gas emissions, thereby contributing to global warming and the acceleration of climate change. As paddy rice farming is one of the largest contributors, and most environmentally damaging farming systems, this will be a particular focus of the book. The mitigation of greenhouse gas emissions needs to be urgently addressed to achieve the 2 degrees Celsius target adopted by COP21 and the 2015 Paris Agreement, but this is not possible if local and national level innovations are not accompanied by international level cooperation, mutual learning and sharing of knowledge and technologies. This book, therefore, brings together international collaborative research on climate-neutral and resilient farming systems compiled by leading scientists and experts from Europe, Asia and Africa. The chapters present evidence-based research and innovative solutions that can be applied or upscaled in different farming systems and regions across the world. Chapters present models and technologies that can be used for practical implementation at the systemic level and advance state of the art knowledge on carbon neutral farming. Combining theory and practice, this interdisciplinary book provides guidance which can inform and increase cooperation between researchers from various countries on climate-neutral and resilient farming systems. Most importantly, the volume provides recommendations which can be put into practice by those working in the agricultural industry, especially in developing countries, where they are attempting to promote climate-neutral and resilient farming systems. The book will be of great interest to students and academics of sustainable agriculture, food security, climate mitigation and sustainable development, in addition to policymakers and practitioners working in these areas.